A Survey on the Catches of Squilla along Kerala Coast - A.K., Kesavan Nair; H., Krishna Iyer (Fishery Technology, 2025)
A stratified random sampling procedure with a centre-day as the sampling unit was found suitable for estimation of squilla landings and catches along the Kerala coast. About 75% of the annual catches were in the period December to April. A time stratification of quarters (3 month period) or one with two seasons (good and lean seasons) were found to yield almost the same annual estimates. The estimated catches of squilla along the Kerala coast for the year 1987 worked out to 32,124 tons with a percentage error of 9.